Osteopontin: The Molecular Bridge between Fat and Cardiac-Renal Disorders - Vianello, Elena; Kalousová, Marta; Dozio, Elena; Tacchini, Lorenza; Zima, Tomáš; Corsi Romanelli, Massimiliano Marco (International journal of molecular sciences, 2020)
Osteopontin (OPN) is a multifaceted matricellular protein, with well-recognized roles in both the physiological and pathological processes in the body. OPN is expressed in the main organs and cell types, in which it induces different biological actions. During physiological conditioning, OPN acts as both an intracellular protein and soluble excreted cytokine, regulating tissue remodeling and immune-infiltrate in adipose tissue the heart and the kidney. In contrast, the increased expression of OPN has been correlated with the severity of the cardiovascular and renal outcomes associated with obesity. Indeed, OPN expression is at the "cross roads" of visceral fat extension, cardiovascular diseases (CVDs) and renal disorders, in which OPN orchestrates the molecular interactions, leading to chronic low-grade inflammation. The common factor associated with OPN overexpression in adipose, cardiac and renal tissues seems attributable to the concomitant increase in visceral fat size and the increase in infiltrated OPN+ macrophages. This review underlines the current knowledge on the molecular interactions between obesity and the cardiac-renal disorders ruled by OPN.
Keywords: nitrobřišní tuk; Insulin Resistance; Kidney Diseases; osteopontin (OPN); inzulinová rezistence; osteopontin; Inflammation; Obesity; chronic kidney disease (CKD); obesity; tuková tkáň; cardiovascular diseases (CVDs); Heart Diseases; Myocardium; obezita; Kidney; Osteopontin; nemoci ledvin; Intra-Abdominal Fat; visceral adipose tissue (VAT); zánět; lidé; renal disorders; Adipose Tissue; Humans; ledviny; nemoci srdce; myokard